On Nie-Tan operator and type-reduction of interval type-2 fuzzy sets - Li, Jiawei; John, Robert; Coupland, Simon; Kendall, Graham (IEEE, 2018)
Type-reduction of type-2 fuzzy sets is considered to be a defuzzification bottleneck because of the computational complexity involved in the process of type-reduction. In this research, we prove that the closed-form Nie-Tan operator, which outputs the average of the upper and lower bounds of the footprint of uncertainty, is actually an accurate method for defuzzifing interval type-2 fuzzy sets.